An inverse design paradigm of multi-functional elastic metasurface via data-driven machine learning. (February 2023) - Zhou, Weijian; Wang, Shuoyuan; Wu, Qian; Xu, Xianchen; Huang, Xinjing; Huang, Guoliang; Liu, Yang; Fan, Zheng
Graphical abstract: Highlights: Propose a data-driven inverse design paradigm of multifunctional elastic metasurface. Demonstrating a dual-functional metasurface with defection and focusing at different frequencies. Abstract: Elastic metasurfaces have become one of the most promising platforms for manipulating mechanical wavefronts with the striking feature of ultra-thin geometry. The conventional design of mechanical metasurfaces significantly relies on numerical, trial-and-error methods to identify structural parameters of the unit cells, which requires huge computational resources and could be extremely challenging if the metasurface is multi-functional. Machine learning technique provides another powerful tool for the design of multi-functional elastic metasurfaces because of its excellent capability in building nonlinear mapping relation between high-dimensional input data and output data. In this paper, a machine learning network is introduced to extract the complex relation between high-dimensional geometrical parameters of the metasurface unit and its high-dimensional dynamic properties. Based on a big dataset, the well-trained network can play the role of a surrogate model in the inverse design of a multi-functional elastic metasurface to significantly shorten the time for the design. Such method can be conveniently extended to design other multi-functional metasurfaces for the manipulation of optical, acoustical or mechanical waves.